2020
DOI: 10.1088/1757-899x/928/7/072033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using Nano iron oxide in radiological shielding

Abstract: In this study, some attenuation parameters of gamma shields were studied. This shields consisting of composite materials of Unsaturated polyester as a base material and Nano iron oxide (Fe2O3) and, micro iron (Fe) as reinforcement materials at different percentages (1, 3,5,7and 9)wt%, and with different thickness (1, 1.5, 2, 2.5, 3, 3.5and 4) cm. The results showed that the use of nanoparticles is better than the microparticales in the field of radiation shielding. It has been shown that the values of attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Iron and/or iron oxide as fillers incorporated into various composites for radiation shielding were investigated in different studies. The results indicated that the attenuation capacity of the prepared composites was enhanced compared with the traditional shielding materials [2,[48][49][50][51][52]. Aluminum and/or aluminum oxide have been investigated as fillers to improve the mechanical properties and radiation shielding effectiveness for different matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…Iron and/or iron oxide as fillers incorporated into various composites for radiation shielding were investigated in different studies. The results indicated that the attenuation capacity of the prepared composites was enhanced compared with the traditional shielding materials [2,[48][49][50][51][52]. Aluminum and/or aluminum oxide have been investigated as fillers to improve the mechanical properties and radiation shielding effectiveness for different matrix composites.…”
Section: Introductionmentioning
confidence: 99%